2022
DOI: 10.3390/bioengineering9110702
|View full text |Cite
|
Sign up to set email alerts
|

Addition of ROCK Inhibitors Alleviates Prostaglandin-Induced Inhibition of Adipogenesis in 3T3L-1 Spheroids

Abstract: To elucidate the additive effects of the ROCK inhibitors (ROCK-i), ripasudil (Rip) and Y27632 on bimatoprost acid (BIM-A), a prostaglandin analog (PG), on adipose tissue, two- and three-dimensional (2D or 3D) cultures of 3T3-L1 cells, the most well characterized cells in the field of lipid research, were used. The cells were subjected to a variety of analyses including lipid staining, real-time cellular metabolic analysis, the mRNA expressions of genes related to adipogenesis and extracellular matrices (ECMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…According to the literature, at a distance greater than 100 µm from the spheroid surface, molecular signaling and glucose concentrations decrease to zero due to diffusion limitation, resulting in cell death [40,45]. In a previous study, a heterogeneous distribution of oil droplets was observed only in 3T3-L1 cells on the surfaces of spheroids with a diameter of 200-300 µm [46]. Our IHC results confirmed elevated levels of adipogenic markers characteristic of differentiated cells, consistent with previous findings in 3T3-L1 cells [47,48].…”
Section: Adipogenic Differentiation Of Hadscs Within Composite Spheroidsmentioning
confidence: 91%
“…According to the literature, at a distance greater than 100 µm from the spheroid surface, molecular signaling and glucose concentrations decrease to zero due to diffusion limitation, resulting in cell death [40,45]. In a previous study, a heterogeneous distribution of oil droplets was observed only in 3T3-L1 cells on the surfaces of spheroids with a diameter of 200-300 µm [46]. Our IHC results confirmed elevated levels of adipogenic markers characteristic of differentiated cells, consistent with previous findings in 3T3-L1 cells [47,48].…”
Section: Adipogenic Differentiation Of Hadscs Within Composite Spheroidsmentioning
confidence: 91%
“…On the other hand, organoids must be formed from stem cells derived from healthy or pathological tissues, having at least one physiological function corresponding to the desired organ and not necessarily showing a spheroidal 3D structure ( Table 1 ). However, most studies of adipogenic 3D models using spheroids still rely on the 3T3-L1 cell lineage (mouse preadipocytes) [ 95 , 96 , 97 , 98 ]. In fact, few articles explored the use of ASCs to form and maturate adipose tissue spheroids [ 99 ], and studies with organoid models are still recent [ 6 , 100 ].…”
Section: Adipose Tissue 3d Modelsmentioning
confidence: 99%